Substrate comprising methylhydrosiloxane composition film or methylhydrosiloxazane composition film in which silica fine particles are dispersed, and method for manufacturing the same
A substrate with a film composed of silica fine particles in a methylhydrosiloxane or methylhydrosiloxazane composition addresses the challenges of cracking and peeling, achieving stable and productive film formation even at high thicknesses and step heights.
Patent Information
- Application Number
- JP2023169901
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2043-09-29
AI Technical Summary
Existing technologies face challenges in forming stable and productive silica films for embedding and planarizing grooves in substrates, particularly due to issues like cracking, peeling, and low productivity, especially when dealing with high step heights and thick film formations.
A substrate with a film composed of silica fine particles dispersed in a methylhydrosiloxane or methylhydrosiloxazane composition, where the average carbon content is between 8 wt% and 18 wt%, and the silica fine particles have an average primary particle size of 5 nm to 150 nm, is used. This film is formed using polymethylhydrosilazane as a matrix material, with specific ratios of Si-H bonds to Si-Me bonds and N-H bonds to Si-Me bonds, which are optimized for adhesion and stability.
The solution enables the formation of a stable film that does not crack or peel, even when the film thickness is 1 μm or more, effectively planarizing substrates with high step heights and improving productivity.
Smart Images

Figure 2025059667000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a substrate comprising a methylhydrosiloxane composition film or a methylhydrosiloxazane composition film having dispersed therein fine silica particles, and a method for producing the same. [Background technology]
[0002] There is a need for a technology to fill and flatten grooves (steps) in a substrate with a silica film that is excellent in stability and productivity without causing cracks or peeling. In general, in semiconductors and liquid crystal panels, elements, wiring, etc. are laminated from the lower layer to the upper layer on a single semiconductor wafer or glass substrate, so it is necessary to flatten protrusions and steps caused by elements, wiring, etc. in order to facilitate the formation of upper layers and to reduce misalignment in the surface direction during lithography. In particular, due to the recent demand for high integration and high definition in semiconductor chips, liquid crystal panels, etc., the height (depth) of these protrusions and steps tends to become larger, sometimes reaching 1 μm or more, so the importance of filling and flattening them is increasing.
[0003] In addition, when manufacturing semiconductor elements using the so-called chip-on-wafer method, which is formed by stacking multiple chips of the same type or different types such as CPUs and memories, which are attracting attention as next-generation semiconductors, it is necessary to mount cut chips on a base wafer, fix the chips, and fill the grooves between adjacent chips. At this time, the depth of the grooves is usually 10 μm or more, and a film that can fill and flatten the grooves is required.
[0004] In addition, a siliceous coating composition used for the purpose of stress relaxation, hardness improvement, heat resistance improvement, thixotropy, etc. has been disclosed (Patent Document 1). The siliceous coating composition includes a matrix member that holds siliceous fine particles in a dispersed state. The carbon content in the siliceous fine particles and the siliceous coating composition is 5 wt% or less.
[0005] Also, a technique for providing a trench-filling composition that is suitable for use in filling a trench formed in a substrate with silicon oxide, and that provides a silicon oxide coating film that has high trench-filling properties, a small cure shrinkage rate, and good crack resistance, has been disclosed (Patent Document 2). In this technique, a trench-filling composition is disclosed that contains a hydrogenated polysilazane compound and a reactant having a structure derived from silica particles. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2019-182893 A [Patent Document 2] JP 2010-177647 A Summary of the Invention [Problem to be solved by the invention]
[0007] By the way, chemical vapor deposition (CVD) is also known as a technique for forming such films. In chemical vapor deposition (CVD), the film is formed to conform to the shape of the substrate, so it is not suitable for filling grooves or flattening. In addition, the film formation speed is slow and productivity is low.
[0008] In addition, when a sol-gel liquid or a siloxane compound containing a bulky organic group such as an ethyl group is used as a matrix material, the volume shrinkage is large because the dehydration reaction occurs during conversion to silica and hardens, and when a thick film of 0.5 μm or more is formed, cracks and peeling are likely to occur, making it difficult to ensure stability and productivity.
[0009] In addition, when polyimide or the like is used as the heat-resistant organic resin, it is difficult to control the shape because of the large thermal changes such as expansion and contraction compared to silica-based materials.In addition, there are manufacturing difficulties such as the decomposition and elution of organic components during the etching and cleaning processes.
[0010] Furthermore, in the technology described in the above prior art documents, a polymer that does not contain any organic groups, such as hydrogenated polysilazane, is used as a matrix material, so that inorganic siliceous material that does not essentially contain or has a small amount of carbon components is formed after heating and curing. Therefore, while it has the advantage of being able to form a film with high hardness and high strength, it has the disadvantage that the stress during heating and curing is large, and cracks and peeling are likely to occur due to bending and thermal changes during and after production. This disadvantage is more pronounced when a substrate having steps is used, rather than on a flat substrate, and when a substrate with even higher steps is used. In addition, since it has low solubility in solvents and high reactivity with moisture, it is difficult to mix uniformly with siliceous fine particles, and there is a problem with the storage stability of the mixed liquid. [Means for solving the problem]
[0011] One aspect of the present invention is a substrate comprising a film having silica fine particles dispersed in a matrix material of a methylhydrosiloxane composition or a methylhydrosiloxazane composition.
[0012] Here, it is preferable that the substrate has a step of 1 μm or more, and the film is embedded at a depth of 1 μm or more from the bottom of the step.
[0013] It is also preferable that the average carbon content of the film is 8 wt % or more and 18 wt % or less.
[0014] The silica fine particles preferably have an average primary particle size of 5 nm or more and 150 nm or less.
[0015] Another aspect of the present invention is a method for manufacturing a substrate, which comprises applying to a substrate a material in which silica fine particles are dispersed in a matrix material of polymethylhydrosilazane or polymethylhydrosiloxazane having a weight-average molecular weight of 400 or more and 20,000 or less, and heating the matrix material.
[0016] The silica fine particles preferably have an average primary particle size of 5 nm or more and 150 nm or less.
[0017] It is also preferable that the mixing ratio (weight ratio) of the silica fine particles to the matrix material is 3 wt % or more and 200 wt % or less.
[0018] It is also preferable that the ratio of Si-H bonds / Si-Me bonds in the structure of the matrix material is 0.3 or more and 0.9 or less, and the ratio of NH bonds / Si-Me bonds is 0.4 or more and 1.1 or less. Effect of the Invention
[0019] According to the present invention, it is possible to provide a film-coated substrate on which a film that does not crack or peel off is formed, particularly a film-coated substrate on which a film that does not crack or peel off even when the film has a thickness of 1 μm or more is formed. [Brief description of the drawings]
[0020] [Figure 1] 1 is a cross-sectional view illustrating a configuration of a film-coated substrate in an embodiment of the present invention. [Diagram 2] 1 is a cross-sectional view illustrating a configuration of a film-coated substrate in an embodiment of the present invention. [Diagram 3] 1 is a cross-sectional view illustrating a configuration of a film-coated substrate in an embodiment of the present invention. [Figure 4] 1 is a cross-sectional view illustrating a configuration of a film-coated substrate in an embodiment of the present invention. [Diagram 5] FIG. 2 is a diagram illustrating a change in composition of a matrix material in an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] [Board configuration] A film-coated substrate 100 according to an embodiment of the present invention is configured by laminating a substrate 10 and a film 12, as shown in FIG.
[0022] The substrate 10 is a member on whose surface the film 12 is formed. The substrate 10 is not particularly limited, but may be, for example, a semiconductor substrate. The substrate 10 may be, for example, a semiconductor substrate on which elements constituting an electric circuit, such as transistors and capacitors, are formed, or a substrate on which a color filter of a liquid crystal panel, etc. is formed.
[0023] The film 12 is formed on the surface of the substrate 10. The film 12 is used as an insulating film, a buried layer, a planarizing film, a passivation film, or the like in the substrate 10 of a semiconductor or liquid crystal panel. Specifically, for example, it is used as an insulating film, a planarizing film, or a buried film for elements constituting an electric circuit such as a transistor or a capacitor, wiring, or a structure constituting a circuit. It is also used to fix upper and lower layers when stacking the semiconductor chips themselves, and as a buried layer or a planarizing film for a groove between chips that is formed when the upper chip is placed. It is also used, for example, as a buried layer or a planarizing film for uneven parts such as color filters of a liquid crystal panel. It is also used, for example, as a passivation film (barrier film) that blocks moisture or oxygen that oxidizes and deteriorates electric circuits and electric elements.
[0024] The film 12 is made of a material in which silica particles are dispersed in a matrix material of a methylhydrosiloxane composition or a methylhydrosiloxazane composition. The methylhydrosiloxane composition is a compound containing H-Si-Me bonds (wherein Me is a methyl group, CH3) bonds in a skeleton of Si-O bonds, and the methylhydrosiloxazane composition is a compound containing Si-O bonds and partially Si-N bonds in a skeleton.
[0025] The reasons for selecting a methylhydrosiloxane composition or a methylhydrosiloxazane composition as the matrix material include: (1) it has a Si-O bond framework similar to that of the silica microparticles and the silicon or glass substrate 10; (2) the Si-Me bonds enable the film 12 to have both strength and flexibility; and (3) the Si-H bonds increase reactivity with the Si-OH bonds on the surface of the silica microparticles and the substrate 10, thereby enhancing adhesion between the silica microparticles and the substrate 10.
[0026] As a material for forming the methylhydrosiloxane composition or methylhydrosiloxazane composition, which is the matrix material, it is preferable to use polymethylhydrosilazane or polymethylhydrosiloxazane having a weight-average molecular weight of 400 to 20,000. If the weight-average molecular weight is less than 400, when the organic solvent mixed and dispersed with the silica fine particles is applied to the base material, the material may flow and not be fixed on the surface of the substrate 10, or the material may evaporate during heating, making it difficult to form a homogeneous film 12. In addition, if the weight-average molecular weight exceeds 20,000, there is a problem that the material is difficult to dissolve in the organic solvent when mixed and dispersed with the silica fine particles.
[0027] In addition, the ratio of Si-H bond / Si-Me bond of polymethylhydrosilazane or polymethylhydrosiloxazane, which is a material forming the methylhydrosiloxane composition or methylhydrosiloxazane composition as the matrix material, is preferably within the range of 0.3 to 0.9. Similarly, the ratio of NH bond / Si-Me bond in polymethylhydrosilazane or polymethylhydrosiloxazane is preferably within the range of 0.4 to 1.1. If the ratio of Si-H bond / Si-Me bond is less than 0.3 or the ratio of NH bond / Si-Me bond is less than 0.4, when the organic solvent mixed and dispersed with silica fine particles is applied to the substrate 10, the adhesion with the substrate 10 and the silica fine particles is reduced, and cracks or peeling may occur in the film 12 after heating. Furthermore, if the ratio of Si-H bonds / Si-Me bonds exceeds 0.9, or if the ratio of NH bonds / Si-Me bonds exceeds 1.1, problems such as an increase in viscosity when mixed and dispersed with silica fine particles in an organic solvent and a decrease in stability during storage of the solution after mixing and dispersion may occur.
[0028] The film 12 preferably has silica particles dispersed therein. The silica particles may be colloidal silica, fused silica, fumed silica, or silica produced by a sintering and crushing method or a vaporization and combustion method. In order to improve dispersibility in an organic solvent, silica particles surface-treated with a silane coupling agent or the like may be used. The silica particles preferably have a primary particle size (average diameter) of 5 nm or more and 150 nm or less. If the primary particle size (average diameter) of the silica particles is less than 5 nm, problems occur such as inability to disperse in an organic solvent due to aggregation, or inability to mix homogeneously with polymethylhydrosilazane or polymethylhydrosiloxazane. If the primary particle size (average diameter) of the silica particles exceeds 150 nm, problems occur such as inability to stably disperse and retain in an organic solvent due to precipitation. In addition, when applied to devices such as liquid crystal panels, the transparency of the film 12 can be increased in the visible light region by setting the primary particle size (average diameter) of the silica particles to 5 nm or more and 150 nm or less.
[0029] The mixing ratio (weight ratio) of silica fine particles to polymethylhydrosilazane or polymethylhydrosiloxazane, which is a material forming the methylhydrosiloxane composition or methylhydrosiloxazane composition as the matrix material, is preferably within the range of 3 wt% to 200 wt%. If the mixing ratio (weight ratio) is less than 3 wt%, problems such as flowing when applied to the substrate 10 and not being able to be fixed to the substrate 10, or cracks occurring in the film 12 after heating may occur. If the mixing ratio (weight ratio) is more than 200 wt%, it may be difficult to form a homogeneous film 12, such as not being able to completely fill the spaces between the fine particles when applied to the substrate 10, leaving only the fine particles exposed from the film 12, or roughness occurring in the film 12.
[0030] The average carbon content, which indicates the mixing ratio of silica particles to the methylhydrosiloxane composition or methylhydrosiloxazane composition of the matrix material, is preferably 8 wt% or more and 18 wt% or less. If the average carbon content is less than 8 wt%, there is a high possibility that cracks or peeling will occur in the formed film 12. Also, if the average carbon content exceeds 18 wt%, there is a possibility that the strength of the formed film 12 will decrease or that shrinkage during the formation process of the film 12 will increase, making it difficult to control the shape of the film 12.
[0031] FIG. 2 shows a schematic cross-sectional view of a substrate 10 having a stepped surface with a film 12 embedded therein, the film 12 having silica particles dispersed in a matrix material of a methylhydrosiloxane composition or a methylhydrosiloxazane composition.
[0032] 2(a) to 2(c) show three cases showing the relationship between the height (depth) H1 of the step of the substrate 10 and the film thickness H2 of the film 12 filled in the step. FIG. 2(a) shows a case where the film thickness H2 of the film 12 filled in the step is smaller than the height (depth) H1 of the step of the substrate 10. FIG. 2(b) shows a case where the height (depth) H1 of the step of the substrate 10 is equal to the film thickness H2 of the film 12 filled in the step. FIG. 2(c) shows a case where the film thickness H2 of the film 12 filled in the step is larger than the height (depth) H1 of the step of the substrate 10.
[0033] 2(a) to 2(c), no cracks or peeling occurred in the film 12 after formation, and a stable film 12 could be formed. In particular, even if the height (depth) H1 of the step provided on the substrate 10 was 1 μm or more and the film thickness H2 of the film 12 embedded in the step was 1 μm or more, no cracks or peeling occurred. That is, according to this embodiment, even if the film thickness of the film 12 was 1 μm or more, no cracks or peeling occurred, and a stable film 12 could be formed.
[0034] Moreover, as shown in Fig. 3, after embedding, the film outside the step can be polished and removed by a method such as CMP to flatten the entire substrate. In this case, it is preferable to form the film 12 so that the film thickness H2 of the film 12 embedded in the step is equal to the height of the step (Fig. 2(b)), or to form the film 12 so that the film thickness H2 of the film 12 embedded in the step is greater than the height of the step (Fig. 2(c)).
[0035] Furthermore, when a method of applying an organic solvent containing polymethylhydrosilazane or polymethylhydrosiloxazane with dispersed silica fine particles to the substrate 10 by a method of fixing the solvent while evaporating, such as spin coating, spray coating, slit coating, gravure coating, or roll coating, is used, the coating liquid essentially flows down from the top of the step to the inside of the step. As a result, as shown in Fig. 4, the film thickness T2 inside the step tends to be larger than the maximum film thickness t1 outside the step of the substrate 10, which is sufficiently distant from the step. Furthermore, the film thicknesses t1 to t4 of the film 12 in the peripheral portion outside the step of the substrate 10 tend to become smaller as they approach the step.
[0036] Here, the pattern provided on the surface of the substrate 10 is not particularly limited in shape, arrangement, and position. For example, the pattern can be a line-shaped, circular, rectangular, or other hole. In particular, the effect of the film 12 is remarkable when the height (depth) H1 of the step of the pattern is 1 μm or more. In addition, the width of the pattern is not particularly limited, but considering the size of the silica fine particles dispersed in the film 12, it is preferable that the minimum width is 30 nm or more. On the other hand, depending on the application, the pattern width can be applied to 1 μm or more or 1 mm or more. Furthermore, the sidewall of the step does not need to be vertical, and may be tapered or inversely tapered.
[0037] [Manufacturing method] In the present embodiment, film 12 is formed by first applying an organic solvent in which silica particles are mixed and dispersed in polymethylhydrosilazane or polymethylhydrosiloxazane to the surface of substrate 10, then scattering and fixing the organic solvent therein, and then heating the resulting film to oxidize polymethylhydrosilazane or polymethylhydrosiloxazane and convert it into a methylhydrosiloxane composition or a methylhydrosiloxazane composition.
[0038] Here, the weight-average molecular weight of polymethylhydrosilazane or polymethylhydrosiloxazane is preferably 400 to 20,000. The average primary particle size of the dispersed silica fine particles is preferably 5 nm to 150 nm. The mixing ratio (weight ratio) of the silica fine particles to the polymethylhydrosilazane or polymethylhydrosiloxazane is preferably within the range of 3 wt% to 200 wt%.
[0039] The ratio of Si-H bond / Si-Me bond in the polymethylhydrosilazane or polymethylhydrosiloxazane is preferably in the range of 0.3 to 0.9, and the ratio of NH bond / Si-Me bond in the polymethylhydrosilazane or polymethylhydrosiloxazane is preferably in the range of 0.4 to 1.1.
[0040] Since polymethylhydrosilazane or polymethylhydrosiloxazane has the property of reacting with moisture and polymerizing, if these organic solvents contain moisture, it may cause problems such as high molecular weight or gelation, which may result in changes in the thickness of film 12 or difficulty in application, so it is preferable to keep the moisture content in the organic solvent to 1 wt % or less.
[0041] The organic solvent is preferably a single or multiple solvents selected from aromatic hydrocarbons such as toluene, xylene, trimethylbenzene, etc.; saturated hydrocarbons such as hexane, hexene, octane, etc.; ethers such as butyl ether, amyl ether, anisole, etc.; esters such as ethyl acetate, propyl acetate, butyl acetate, etc.; and ketones such as diethyl ketone, methyl isobutyl ketone, cyclohexanone, etc.
[0042] The organic solvent containing polymethylhydrosilazane or polymethylhydrosiloxazane having silica fine particles dispersed therein can be applied to the substrate 10 by a method in which the solvent is fixed while being evaporated, such as spin coating, spray coating, slit coating, gravure coating, roll coating, etc. However, the application method is not limited to these.
[0043] In addition, when filling deep grooves or steps of several micrometers or more, a mixture of polymethylhydrosiloxane or polymethylhydrosiloxazane and silica fine particles is applied to a substrate, the organic solvent is evaporated to fix the mixture, and then a series of heating operations is repeated several times to form a thick film. It is possible to form a film of several micrometers or more at once, but this requires increasing the viscosity of the coating liquid, which prevents the coating liquid and coating device from becoming difficult to handle.
[0044] An organic solvent containing polymethylhydrosilazane or polymethylhydrosiloxazane in which silica fine particles are dispersed is applied to the substrate 10, and the organic solvent is evaporated and fixed, and then a heat treatment is performed. The heating method is not particularly limited, but for example, an oven or a hot plate can be used. The heating temperature is preferably 150° C. or higher and 600° C. or lower. The atmosphere during heating is preferably an oxidizing gas such as air, oxygen, or water vapor. Dry nitrogen, argon, or the like may be used as a balance gas.
[0045] FIG. 5 is a diagram showing the estimated change in the structure of the matrix before and after heating. In FIG. 5, a, b, c, k, and x, y, z are present randomly. Before heating, polymethylhydrosilazane is composed of a, b, c, and polymethylhydrosiloxazane is composed of a, b, c, and k. Here, the composition ratios of a, b, c, and k are a: 5% to 70%, b: 10% to 60%, c: 3% to 20%, and k: 0% to 15%. After heating, some or all of the Si-N bonds are oxidized, and the composition is composed of x and y in the case of methylhydrosiloxane composition, and x, y, and z in the case of methylhydrosiloxazane composition. Here, the composition ratios of x, y, and z are x: 1% to 20%, y: 70% to 100%, and z: 0% to 20%. The composition ratios are combined so that there is no contradiction in each combination. For example, when y is 100%, the other x and z are 0%.
[0046] [Example] [Synthesis of polymethylhydrosilazane A] A stainless steel autoclave with a capacity of 2 L was equipped with a stirrer, a nozzle capable of injecting and discharging a chemical or gas into the liquid phase and the gas phase, and a cooling and control device capable of controlling the temperature of the contents. After thoroughly drying the inside of the autoclave using dry nitrogen, 300 g of toluene and 300 g of pyridine that had been dehydrated with a molecular sieve were injected and cooled to 0°C while stirring. 50 g of methylhydrodichlorosilane was gradually injected into this, and 50 g of dry ammonia was injected over 2 hours while maintaining the temperature at 0°C. After injecting dry nitrogen to remove excess ammonia, the reaction liquid was filtered through a SUS316 filter with a filtration accuracy of 25 μm. The obtained filtrate was mixed with 500 g of toluene that had been dried with a molecular sieve, and this was distilled in a rotary evaporator with a bath temperature of 50°C until the contents became approximately 200 g. This was mixed with 200 g of dried toluene, and the solvent was thoroughly removed using a rotary evaporator also at a bath temperature of 50° C., yielding about 15 g of a viscous liquid.
[0047] The viscous liquid was measured by 1H-NMR (400MHz) using CDCl3 as a lock solvent, and the following peaks were observed: Si-Me bond peak at 0.1-0.2ppm, NH bond peak at 0.4-1.8ppm, and Si-H bond peak at 4.1-5.1ppm. The integral ratio of each peak (based on the number of protons) was 0.82 for Si-H bond / Si-Me bond, and 0.75 for NH bond / Si-Me bond.
[0048] In addition, when the viscous liquid was applied to a KBr plate and the FTIR spectrum was measured using an FTIR device (Jasco: Model FT / IR-4100), the peaks at 1,180 and 3,370 cm, which are assigned to NH bonds, were observed. -1 Absorption at 1,260 cm, which is attributed to the Si-Me bond -1 Absorption at 2,160 cm, which is attributed to the Si-H bond -1 Absorption at 2,970cm, which is attributed to the CH bond -1 Absorption was observed.
[0049] Furthermore, when the viscous liquid was subjected to GPC measurement, the weight average molecular weight was found to be 850 in terms of polystyrene.
[0050] From the above analytical results, the obtained viscous liquid was identified as polymethylhydrosilazane.
[0051] [Synthesis of polymethylhydrosilazane B] A stainless steel autoclave with a capacity of 2 L was equipped with a stirrer, a nozzle capable of injecting and discharging a chemical or gas into the liquid phase and the gas phase, and a cooling and control device capable of controlling the temperature of the contents. After thoroughly drying the inside of the autoclave with dry nitrogen, 300 g of toluene and 300 g of pyridine that had been dehydrated with a molecular sieve were injected and cooled to 0°C while stirring. 20 g of methylhydrodichlorosilane and 30 g of methyltrichlorosilane were gradually injected into the autoclave, and 50 g of dry ammonia was injected over 2 hours while maintaining the temperature at 0°C. After injecting dry nitrogen to remove excess ammonia, the reaction liquid was filtered with a SUS316 filter with a filtration accuracy of 25 μm. The obtained filtrate was mixed with 500 g of toluene that had been dried with a molecular sieve, and this was distilled in a rotary evaporator with a bath temperature of 50°C until the contents became approximately 200 g. This was mixed with 200 g of dried toluene, and the solvent was thoroughly removed using a rotary evaporator similarly at a bath temperature of 50° C., yielding about 18 g of a viscous liquid.
[0052] The viscous liquid was measured by 1H-NMR (400MHz) using CDCl3 as a lock solvent, and a peak at 0.1-0.2ppm attributable to Si-Me bonds, a peak at 0.4-1.8ppm attributable to NH bonds, and a peak at 4.1-5.1ppm attributable to Si-H bonds were observed. From the integral ratio of each peak (based on the number of protons), the ratio of Si-H bonds / Si-Me bonds was 0.39, and the ratio of NH bonds / Si-Me bonds was 1.05.
[0053] In addition, when the viscous liquid was applied to a KBr plate and the FTIR spectrum was measured using an FTIR device (Jasco: Model FT / IR-4100), the peaks at 1,180 and 3,370 cm, which are assigned to NH bonds, were observed. -1 Absorption at 1,260 cm, which is attributed to the Si-Me bond -1 Absorption at 2,160 cm, which is attributed to the Si-H bond -1 Absorption at 2,970cm, which is attributed to the CH bond -1 Absorption was observed.
[0054] Furthermore, when the viscous liquid was subjected to GPC measurement, the weight average molecular weight in terms of polystyrene was found to be 1,800.
[0055] From the above analytical results, the obtained viscous liquid was identified as polymethylhydrosilazane.
[0056] [Synthesis of polymethylhydrosiloxazane C] A stainless steel autoclave with a capacity of 2 L was equipped with a stirrer, a nozzle capable of injecting and discharging a chemical or gas into the liquid phase and the gas phase, and a cooling and control device capable of controlling the temperature of the contents. After thoroughly drying the inside of the autoclave with dry nitrogen, 50 g of pyridine dehydrated with a molecular sieve was injected and cooled to 0°C while stirring. A solution in which 12 g of polymethylhydrosilazane A obtained above was dissolved in 90 g of toluene dehydrated with a molecular sieve was gradually injected into the autoclave. Next, 40 g of pyridine dehydrated with a molecular sieve and 0.5 g of pure water were mixed, and this was injected over 1 hour into the autoclave in which polymethylhydrosilazane A was dissolved in pyridine and toluene. Dry nitrogen was injected to replace the inside of the autoclave, and the contents were filtered through a 5 μm Teflon (registered trademark) filter. The obtained filtrate was mixed with 100 g of toluene dried with molecular sieves, and this was distilled in a rotary evaporator with a bath temperature of 50° C. until the content became about 80 g. This was mixed with 100 g of dried toluene, and the solvent was sufficiently distilled off in a rotary evaporator also with a bath temperature of 50° C., obtaining about 12 g of a viscous liquid.
[0057] The viscous liquid was measured by 1H-NMR (400MHz) using CDCl3 as a lock solvent, and the following peaks were observed: Si-Me bond peak at 0.1-0.2ppm, NH bond peak at 0.4-1.8ppm, and Si-H bond peak at 4.1-5.1ppm. The integral ratio of each peak (based on the number of protons) was 0.63 for Si-H bond / Si-Me bond, and 0.73 for NH bond / Si-Me bond.
[0058] In addition, when the viscous liquid was applied to a KBr plate and the FTIR spectrum was measured using an FTIR device (Jasco: Model FT / IR-4100), the 1,120 cm -1 Absorption at 1,180 and 3,370 cm, which are assigned to the NH bond -1 Absorption at 1,250 cm, which is attributed to the Si-Me bond -1 Absorption at 2,160 cm, which is attributed to the Si-H bond -1 Absorption at 2,970cm, which is attributed to the CH bond -1 Absorption was observed.
[0059] Furthermore, when this viscous liquid was subjected to GPC measurement, the weight average molecular weight in terms of polystyrene was found to be 11,500.
[0060] From the above analytical results, the obtained viscous liquid was identified as polymethylhydrosiloxane.
[0061] [Synthesis of polymethylsilazane] A stainless steel autoclave with a capacity of 2 L was equipped with a stirrer, a nozzle capable of injecting and discharging a chemical or gas into the liquid phase and the gas phase, and a cooling and control device capable of controlling the temperature of the contents. After thoroughly drying the inside of the autoclave with dry nitrogen, 300 g of toluene and 300 g of pyridine that had been dehydrated with a molecular sieve were injected and cooled to 0°C while stirring. 25 g of dimethyldichlorosilane and 30 g of methyltrichlorosilane were gradually injected into the autoclave, and 50 g of dry ammonia was injected over 2 hours while maintaining the temperature at 0°C. After injecting dry nitrogen to remove excess ammonia, the reaction liquid was filtered through a SUS316 filter with a filtration accuracy of 25 μm. The obtained filtrate was mixed with 500 g of toluene that had been dried with a molecular sieve, and this was distilled in a rotary evaporator with a bath temperature of 50°C until the contents became approximately 200 g. This was mixed with 200 g of dried toluene, and the solvent was thoroughly removed using a rotary evaporator similarly set at a bath temperature of 50° C., yielding about 20 g of a viscous liquid.
[0062] When the obtained viscous liquid was measured by 1H-NMR (400MHz) using CDCl3 as a lock solvent, a peak at 0.1 to 0.2 ppm attributed to Si-Me bonds and a peak at 0.4 to 1.8 ppm attributed to NH bonds were observed. From the integral ratio of each peak (based on the number of protons), the ratio of NH bonds / Si-Me bonds was 1.22. In addition, no peaks at 4.1 to 5.1 ppm attributed to Si-H bonds were observed.
[0063] In addition, when the viscous liquid was applied to a KBr plate and the FTIR spectrum was measured using an FTIR device (Jasco: Model FT / IR-4100), the peaks at 1,180 and 3,370 cm, which are assigned to NH bonds, were observed. -1 Absorption at 1,260 cm, which is attributed to the Si-Me bond -1 Absorption at 2,970cm, which is attributed to the CH bond -1 The absorption of 2,160 cm, which is attributed to the Si-H bond, was observed. -1 No absorption was observed.
[0064] Furthermore, when this viscous liquid was subjected to GPC measurement, the weight average molecular weight in terms of polystyrene was found to be 2,400.
[0065] From the above analysis results, the obtained viscous liquid was identified as polymethylsilazane.
[0066] [Synthesis of hydrogenated polysilazane] A stainless steel reactor with a capacity of 2 L and equipped with a stirrer and a cooling device was thoroughly dried with dry nitrogen, and then 1,500 g of pyridine dried with molecular sieves was added and cooled to 0°C while stirring. 120 g of dichlorosilane was added to this over 1 hour to form a pyridine-dichlorosilane complex. Next, 120 g of dry ammonia was injected over 5 hours while stirring while maintaining the temperature at 0°C. After the reaction was completed, the slurry product was filtered with a SUS316 filter with a filtration accuracy of 25 μm under a dry nitrogen atmosphere to obtain 1,000 g of filtrate. This was distilled under reduced pressure using a rotary evaporator with a bath temperature of 40°C to obtain 30 g of a viscous liquid.
[0067] In addition, when the viscous liquid was applied to a KBr plate and the FTIR spectrum was measured using an FTIR device (Jasco: Model FT / IR-4100), the peaks at 1,180 and 3,370 cm assigned to the NH bond were observed. -1 Absorption at 2,160 cm, which is attributed to the Si-H bond -1 Absorption of 850 to 1,050 cm, which is attributed to Si-H or Si-N bonds -1 The absorption at 1,260 cm was observed, which is attributed to the Si-Me bond. -1 and 2,970 cm -1 No absorption was observed.
[0068] Furthermore, when this viscous liquid was subjected to GPC measurement, the weight average molecular weight in terms of polystyrene was found to be 1,500.
[0069] From the above analytical results, the obtained viscous liquid was identified as hydrogenated polysilazane.
[0070] [Example 1] 20 g of colloidal silica (Nissan Chemical Industries, Ltd., organosilica sol MEK-ST-L: average particle size 45 nm, solid content concentration 30%) and 50 g of butyl acetate (Tokyo Chemical Industry, Ltd.: A0024, purity >99%) were mixed and stirred in a 300 ml glass container, and 20 g of thoroughly dried molecular sieve 4A was added and left at room temperature for one day to dehydrate. This was then distilled in a rotary evaporator with a bath temperature of 50° C. until the content was reduced to approximately 30 g.
[0071] Next, 100 g of dried butyl acetate was mixed and distilled in a rotary evaporator at the same bath temperature of 50° C. until the content became 25 g. After cooling at room temperature, 6 g of polymethylhydrosilazane A was mixed and stirred well, and filtered through a Teflon (registered trademark) membrane filter with a filtration accuracy of 1 μm to obtain a mixed dispersion of colloidal silica and polymethylhydrosilazane A. Note that the mixing ratio of colloidal silica (solid content) to polymethylhydrosilazane A under these conditions was 100 wt %.
[0072] The mixed dispersion was dropped onto a 4-inch silicon wafer and spin-coated at 500 rpm for 30 seconds. The wafer was then placed on a hot plate heated to 300°C in air for 10 minutes and allowed to cool, forming a homogeneous thin film without cracks or peeling.
[0073] The silicon wafer with the film was cut, and the cross section was observed (magnification 10,000 to 80,000 times) with a SEM using a JEOL model JSM-IT800. As a result, the formation of a film with a thickness of 2.1 μm in which silica particles with a diameter of 50 to 110 nm were distributed evenly was confirmed. Furthermore, the elemental composition in the film was measured by X-ray photoelectron spectroscopy (after the surface was sputtered) using a photoelectron spectrometer (ESCA) manufactured by JEOL Ltd., and the carbon content (calculated as the amount of carbon atoms relative to the silica equivalent) was 13.1 wt%. Furthermore, the FTIR spectrum of the film was measured using an FTIR device (Jasco model FT / IR-4100) by a method of subtracting the silicon wafer absorption as the background. As a result, the 470 and 980 to 1,270 cm attributable to Si-O bonds were -1 Absorption at 1,260 cm, which is attributed to the Si-Me bond -1 Absorption at 2,160 cm, which is attributed to the Si-H bond -1 Absorption at 2,970cm, which is attributed to the CH bond -1 From this, the composition of the film was identified as methylhydrosiloxane.
[0074] [Example 2] The same operation as in Example 1 was carried out except that polymethylhydrosilazane B was used instead of polymethylhydrosilazane A, to obtain a mixed dispersion of colloidal silica and polymethylhydrosilazane B. Note that, under these conditions, the mixing ratio of colloidal silica (solid content) to polymethylhydrosilazane B was 100 wt %.
[0075] The mixed dispersion was dropped onto a 4-inch silicon wafer and spin-coated at 500 rpm for 30 seconds. The wafer was then placed on a hot plate heated to 300°C in air for 10 minutes and allowed to cool, forming a homogeneous thin film without cracks or peeling.
[0076] The silicon wafer with the film was cut, and the cross section was observed (magnification 10,000 to 80,000 times) with a SEM using a JEOL model JSM-IT800. As a result, the formation of a film with a thickness of 2.3 μm in which silica particles with a diameter of 40 to 100 nm were distributed evenly was confirmed. Furthermore, the elemental composition in the film was measured by X-ray photoelectron spectroscopy (after the surface was sputtered) using a photoelectron spectrometer (ESCA) manufactured by JEOL Ltd., and the carbon content (calculated as the amount of carbon atoms relative to the silica equivalent) was 16.8 wt%. Furthermore, the FTIR spectrum of the film was measured using an FTIR device (Jasco model FT / IR-4100) by a method of subtracting the silicon wafer absorption as the background. As a result, the 470 and 980 to 1,270 cm attributable to Si-O bonds were -1 Absorption at 3,370 cm, which is attributed to the NH bond -1 Absorption at 1,260 cm, which is attributed to the Si-Me bond -1 Absorption at 2,160 cm, which is attributed to the Si-H bond -1 Absorption at 2,970cm, which is attributed to the CH bond -1 From this, the composition of the film was identified as methylhydrosiloxazane.
[0077] [Example 3] The same operation as in Example 1 was carried out, except that polymethylhydrosiloxazane C was used instead of polymethylhydrosilazane A, to obtain a mixed dispersion of colloidal silica and polymethylhydrosiloxazane C. Note that, under these conditions, the mixing ratio of colloidal silica (solid content) to polymethylhydrosiloxazane C was 100 wt %.
[0078] The mixed dispersion was dropped onto a 4-inch silicon wafer and spin-coated at 500 rpm for 30 seconds. The wafer was then placed on a hot plate heated to 300°C in air for 10 minutes and allowed to cool, forming a homogeneous thin film without cracks or peeling.
[0079] The silicon wafer with the film was cut, and the cross section was observed (magnification 10,000 to 80,000 times) with a SEM using a JEOL model JSM-IT800. As a result, the formation of a film with a thickness of 2.1 μm in which silica particles with a diameter of 40 to 110 nm were distributed evenly was confirmed. Furthermore, the elemental composition in the film was measured by X-ray photoelectron spectroscopy (after the surface was sputtered) using a photoelectron spectrometer (ESCA) manufactured by JEOL Ltd., and the carbon content (calculated as the amount of carbon atoms relative to the silica equivalent) was 10.8 wt%. Furthermore, the FTIR spectrum of the film was measured using an FTIR device (Jasco model FT / IR-4100) by a method of subtracting the silicon wafer absorption as the background. As a result, the 470 and 980 to 1,270 cm attributable to Si-O bonds were -1 Absorption at 1,260 cm, which is attributed to the Si-Me bond -1 Absorption at 2,160 cm, which is attributed to the Si-H bond -1 Absorption at 2,970cm, which is attributed to the CH bond -1 From this, the composition of the film was identified as methylhydrosiloxane.
[0080] [Example 4] The same operation as in Example 1 was carried out except that 20 g of colloidal silica (organosilica sol MEK-ST manufactured by Nissan Chemical Industries, Ltd.: average particle size 12 nm, solid content concentration 30%) was used instead of 20 g of colloidal silica (organosilica sol MEK-ST-L manufactured by Nissan Chemical Industries, Ltd.: average particle size 45 nm, solid content concentration 30%), to obtain a mixed dispersion of colloidal silica and polymethylhydrosilazane A. Note that the mixing ratio of colloidal silica (solid content) to polymethylhydrosilazane A under these conditions was 100 wt%.
[0081] The mixed dispersion was dropped onto a 4-inch silicon wafer and spin-coated at 500 rpm for 30 seconds. The wafer was then placed on a hot plate heated to 300°C in air for 10 minutes and allowed to cool, forming a homogeneous thin film without cracks or peeling.
[0082] The silicon wafer with the film was cut, and the cross section was observed (magnification 10,000 to 80,000 times) with a SEM using a JEOL model JSM-IT800. As a result, the formation of a film with a thickness of 1.8 μm in which silica particles with a diameter of 7 to 20 nm were distributed evenly was confirmed. Furthermore, the elemental composition in the film was measured by X-ray photoelectron spectroscopy (after the surface was sputtered) using a photoelectron spectrometer (ESCA) manufactured by JEOL Ltd., and the carbon content (calculated as the amount of carbon atoms relative to the silica equivalent) was 12.2 wt%. Furthermore, the FTIR spectrum of the film was measured using an FTIR device (Jasco model FT / IR-4100) by a method of subtracting the silicon wafer absorption as the background. As a result, the 470 and 980 to 1,270 cm attributable to Si-O bonds were -1 Absorption at 1,260 cm, which is attributed to the Si-Me bond -1 Absorption at 2,160 cm, which is attributed to the Si-H bond -1 Absorption at 2,970cm, which is attributed to the CH bond -1 From this, the composition of the film was identified as methylhydrosiloxane.
[0083] [Example 5] The same operation as in Example 1 was carried out except that the amount of colloidal silica (organosilica sol MEK-ST-L manufactured by Nissan Chemical Industries, Ltd.: average particle size 45 nm, solid content concentration 30%) was changed to 2 g and the amount of polymethylhydrosilazane A mixed was changed to 12 g, to obtain a mixed dispersion of colloidal silica and polymethylhydrosilazane A. Note that the mixing ratio of colloidal silica (solid content) to polymethylhydrosilazane A under these conditions was 5.0 wt%.
[0084] The mixed dispersion was dropped onto a 4-inch silicon wafer and spin-coated at 500 rpm for 30 seconds. The wafer was then placed on a hot plate heated to 300°C in air for 10 minutes and allowed to cool, forming a homogeneous thin film without cracks or peeling.
[0085] The silicon wafer with the film was cut, and the cross section was observed (magnification 10,000 to 80,000 times) with a SEM using a JEOL model JSM-IT800. As a result, the formation of a film with a thickness of 1.5 μm in which silica particles with a diameter of 40 to 110 nm were distributed sparsely but evenly was confirmed. In addition, the elemental composition in the film was measured by X-ray photoelectron spectroscopy (after the surface was sputtered) using a photoelectron spectrometer (ESCA) manufactured by JEOL Ltd., and the carbon content (calculated as the amount of carbon atoms relative to the silica equivalent) was 17.8 wt%. In addition, the FTIR spectrum of the film was measured using an FTIR device (Jasco model FT / IR-4100) by a method of subtracting the silicon wafer absorption as the background. As a result, the 470 and 980 to 1,270 cm attributable to Si-O bonds were -1 Absorption at 3,370 cm, which is attributed to the NH bond -1 Absorption at 1,260 cm, which is attributed to the Si-Me bond -1 Absorption at 2,160 cm, which is attributed to the Si-H bond -1 Absorption at 2,970cm, which is attributed to the CH bond -1 From this, the composition of the film was identified as methylhydrosiloxazane.
[0086] [Example 6] The same operation as in Example 1 was carried out except that the amount of colloidal silica (organosilica sol MEK-ST-L manufactured by Nissan Chemical Industries, Ltd.: average particle size 45 nm, solid content concentration 30%) was changed to 25 g and the amount of polymethylhydrosilazane A mixed was changed to 4 g, to obtain a mixed dispersion of colloidal silica and polymethylhydrosilazane A. Note that the mixing ratio of colloidal silica (solid content) to polymethylhydrosilazane A under these conditions was 187.5 wt%.
[0087] The mixed dispersion was dropped onto a 4-inch silicon wafer and spin-coated at 500 rpm for 30 seconds. The wafer was then placed on a hot plate heated to 300°C in air for 10 minutes and allowed to cool, forming a homogeneous thin film without cracks or peeling.
[0088] The silicon wafer with the film was cut, and the cross section was observed (magnification 10,000 to 80,000 times) with a SEM using a JEOL model JSM-IT800. As a result, the formation of a film with a thickness of 1.9 μm in which silica particles with a diameter of 50 to 110 nm were distributed evenly was confirmed. Furthermore, the elemental composition in the film was measured by X-ray photoelectron spectroscopy (after the surface was sputtered) using a photoelectron spectrometer (ESCA) manufactured by JEOL Ltd., and the carbon content (calculated as the amount of carbon atoms relative to the silica equivalent) was 8.1 wt%. Furthermore, the FTIR spectrum of the film was measured using an FTIR device (Jasco model FT / IR-4100) by a method of subtracting the silicon wafer absorption as the background. As a result, the 470 and 980 to 1,270 cm attributable to Si-O bonds were -1 Absorption at 1,260 cm, which is attributed to the Si-Me bond -1 Absorption at 2,160 cm, which is attributed to the Si-H bond -1 Absorption at 2,970cm, which is attributed to the CH bond -1 From this, the composition of the film was identified as methylhydrosiloxane.
[0089] [Example 7] The mixed dispersion of colloidal silica and polymethylhydrosilazane B shown in Example 2 was dropped onto a silicon wafer on which linear grooves of 40 μm in width and 30 μm in depth at their deepest point were formed, and spin-coated at a rotation speed of 500 rpm for 30 seconds. This was held on a hot plate heated to 300° C. in the atmosphere for 10 minutes and then allowed to cool, forming a thin film without cracks or peeling.
[0090] The silicon wafer with the film was cut, and the cross section of the straight groove was observed with a JEOL model JSM-IT800 under SEM (magnification 10,000 to 80,000 times), revealing that the film thickness (H2) at the center of the groove width was 12.5 μm, and the film thickness outside the groove (part 2 mm away from the groove end) was 2.2 μm, and a thin film was confirmed in which silica particles with diameters of 50 to 110 nm were distributed evenly both inside and outside the groove. Furthermore, no cracks or peeling were observed under SEM observation.
[0091] [Comparative Example 1] A mixed dispersion of colloidal silica and polymethylsilazane was obtained by the same procedure as in Example 2, except that polymethylsilazane was used instead of polymethylhydrosilazane B. The mixed dispersion obtained was dropped onto a silicon wafer on which linear grooves of 40 μm in width and 30 μm in depth at the deepest part were formed, and spin-coated at a rotation speed of 500 rpm for 30 seconds. This was held on a hot plate heated to 300° C. in the atmosphere for 10 minutes, and then allowed to cool, forming a thin film.
[0092] Visual observation of the formed thin film confirmed peeling and cracks starting from the grooves. The silicon wafer with the film was cut, and the cross section of the linear grooves was observed with a SEM (magnification 10,000-80,000 times) using a JEOL model JSM-IT800. Peeling of the film from the substrate was observed inside the grooves, and it was impossible to measure the film thickness. The film thickness in the part outside the groove where peeling had not occurred (part 2 mm away from the end of the groove) was 1.9 μm. Also, a thin film with particles of 50-110 nm in diameter distributed evenly was confirmed outside the grooves.
[0093] [Comparative Example 2] A mixed dispersion of colloidal silica and hydrogenated polysilazane was obtained by the same procedure as in Example 2, except that hydrogenated polysilazane was used instead of polymethylhydrosilazane B. The mixed dispersion obtained was dropped onto a silicon wafer on which linear grooves with a width of 40 μm and a maximum depth of 30 μm were formed, and spin-coated at a rotation speed of 500 rpm for 30 seconds. This was held for 10 minutes on a hot plate heated to 300° C. in the atmosphere and then allowed to cool, forming a thin film.
[0094] Visual observation of the formed thin film confirmed numerous peelings and cracks over the entire surface of the substrate. This silicon wafer with the thin film was cut, and the cross section of the linear groove was observed with a JEOL model JSM-IT800 under SEM (magnification 10,000 to 80,000 times). Peeling of the film from the substrate was observed both inside and outside the groove, making it impossible to measure the film thickness.
[0095] [Configuration of the invention] [Configuration 1] A substrate comprising a film having silica fine particles dispersed in a matrix material of a methylhydrosiloxane composition or a methylhydrosiloxazane composition. [Configuration 2] 2. The substrate according to claim 1, The substrate has a step of 1 μm or more, A substrate, characterized in that the film is buried at a depth of 1 μm or more from the bottom of the step. [Configuration 3] The substrate according to configuration 1 or 2, A substrate characterized in that the average carbon content of the film is 8 wt % or more and 18 wt % or less. [Configuration 4] The substrate according to any one of configurations 1 to 3, The substrate is characterized in that the silica fine particles have an average primary particle size of 5 nm or more and 150 nm or less. [Configuration 5] A method for manufacturing a substrate, comprising the steps of: A method for manufacturing a substrate, comprising applying to a substrate a material in which silica fine particles are dispersed in a matrix material of polymethylhydrosilazane or polymethylhydrosiloxazane having a weight average molecular weight of 400 or more and 20,000 or less, and heating the material. [Configuration 6] A method for producing a substrate according to configuration 5, comprising the steps of: The method for manufacturing a substrate, wherein the silica fine particles have an average primary particle size of 5 nm or more and 150 nm or less. [Configuration 7] A method for producing a substrate according to configuration 5 or 6, comprising the steps of: A method for manufacturing a substrate, wherein a mixing ratio (weight ratio) of the silica fine particles to the matrix material is 3 wt % or more and 200 wt % or less. [Configuration 8] A method for producing a substrate according to any one of configurations 5 to 7, comprising the steps of: A method for manufacturing a substrate, wherein a ratio of Si-H bonds / Si-Me bonds in the structure of the matrix material is 0.3 or more and 0.9 or less, and a ratio of NH bonds / Si-Me bonds is 0.4 or more and 1.1 or less. [Explanation of symbols]
[0096] 10 substrate, 12 membrane, 100 substrate with membrane.
Claims
1. A substrate comprising a film having silica fine particles dispersed in a matrix material of a methylhydrosiloxane composition or a methylhydrosiloxazane composition.
2. 2. The substrate of claim 1 , The substrate has a step of 1 μm or more, A substrate, characterized in that the film is embedded 1 μm or more from the bottom of the step.
3. 3. The substrate according to claim 1 or 2, The substrate, wherein the average carbon content of the film is 8 wt % or more and 18 wt % or less.
4. The substrate according to any one of claims 1 to 3, The silica fine particles have an average primary particle size of 5 nm or more and 150 nm or less.
5. A method for manufacturing a substrate, comprising the steps of: A method for manufacturing a substrate, comprising applying to a substrate a material in which silica fine particles are dispersed in a matrix material of polymethylhydrosilazane or polymethylhydrosiloxazane having a weight average molecular weight of 400 or more and 20,000 or less, and heating the material.
6. A method for manufacturing a substrate according to claim 5, comprising the steps of: The method for manufacturing a substrate, wherein the silica fine particles have an average primary particle size of 5 nm or more and 150 nm or less.
7. A method for manufacturing a substrate according to claim 5 or 6, comprising the steps of: A method for manufacturing a substrate, wherein a mixing ratio (weight ratio) of said silica fine particles to said matrix material is 3 wt % or more and 200 wt % or less.
8. A method for manufacturing a substrate according to claim 5 or 6, comprising the steps of: A method for manufacturing a substrate, wherein a ratio of Si-H bonds / Si-Me bonds in the structure of the matrix material is 0.3 or more and 0.9 or less, and a ratio of N-H bonds / Si-Me bonds is 0.4 or more and 1.1 or less.
Citation Information
Patent Citations
Coating film, member coated with the same and method for producing the coating film
JP2002105676A
Fluorescent sealing sheet, light emitting diode device, and manufacturing method of light emitting diode device
JP2013214716A
Curable composition and semiconductor device using the composition as sealing agent
JP2021080348A
Polysilazane-based composition for being filled in trench
JP2010177647A
Siliceous coating composition, light transmitting member and forming method of siliceous coating layer
JP2019182893A